Here's the question you clicked on:
114325
write (27a^-9)^-2/3 in simplest form please help me ive been stuck on this for like 20 minutes now
\[(27a^{-9})^{-\frac{2}{3}} = 27^{-\frac{2}{3}}(a^{-9})^{-\frac{2}{3}} = (3^3)^{-\frac{2}{3}}(a^{-9})^{-\frac{2}{3}}\] \[=3^{-3\frac{2}{3}}a^{-9\frac{-2}{3}} = 3^{-2}a^{6} = \frac{1}{3^2}a^6= \frac{1}{9}a^6\]
@amistre64 Could you please validate my solution? Thank you in advance!
I think my solution is valid if a is positive.
even if a is negative its fine
Thank you very much!